Metagenomic Insights Into the Changes of Antibiotic Resistance and Pathogenicity Factor Pools Upon Thermophilic Composting of Human Excreta - Werner, Katharina A.; Schneider, Dominik; Poehlein, Anja; Diederich, Nina; Feyen, Lara; Axtmann, Katharina; Hübner, Tobias; Brüggemann, Nicolas; Prost, Katharina; Daniel, Rolf; Grohmann, Elisabeth (Frontiers in Microbiology, 2022)
In times of climate change, practicing a form of sustainable, climate-resilient and productive agriculture is of primordial importance. Compost could be one form of sustainable fertilizer, which is increasing humus, water holding capacity, and nutrient contents of soils. It could thereby strengthen agriculture towards the adverse effects of climate change, especially when additionally combined with biochar. To get access to sufficient amounts of suitable materials for composting, resources, which are currently treated as waste, such as human excreta, could be a promising option. However, the safety of the produced compost regarding human pathogens, pharmaceuticals (like antibiotics) and related resistance genes must be considered. In this context, we have investigated the effect of 140- and 154-days of thermophilic composting on the hygienization of human excreta and saw dust from dry toilets together with straw and green cuttings with and without addition of biochar. Compost samples were taken at the beginning and end of the composting process and metagenomic analysis was conducted to assess the fate of antibiotic resistance genes (ARGs) and pathogenicity factors of the microbial community over composting. Potential ARGs conferring resistance to major classes of antibiotics, such as beta-lactam antibiotics, vancomycin, the MLSB group, aminoglycosides, tetracyclines and quinolones were detected in all samples. However, relative abundance of ARGs decreased from the beginning to the end of composting. This trend was also found for genes encoding type III, type IV, and type VI secretion systems, that are involved in pathogenicity, protein effector transport into eukaryotic cells and horizontal gene transfer between bacteria, respectively. The results suggest that the occurrence of potentially pathogenic microorganisms harboring ARGs declines during thermophilic composting. Nevertheless, ARG levels did not decline below the detection limit of quantitative PCR (qPCR). Thresholds for the usage of compost regarding acceptable resistance gene levels are yet to be evaluated and defined.